To be or not to be: postcubital vein in insects revealed by microtomography. (1st November 2019) - Schubnel, Thomas; Desutter‐Grandcolas, Laure; Legendre, Frederic; Prokop, Jakub; Mazurier, Arnaud; Garrouste, Romain; Grandcolas, Philippe; Nel, Andre
Abstract: To better understand insect evolution, fossils – mainly known by their wings – must be used as terminals in phylogenetic analyses. Such analyses are, however, rarely performed because of a lack of consensus on the homology of venation in insects. Researchers do not agree with the current concept on the exact number and identity of the main veins. Here, we confirm the presence, which has been in question since the early 20th century, of an independent main postcubital vein (PCu vein) between the cubital and anal veins (29 fossil and extant examined orders; > 85% of observed insects). The PCu vein corresponds to the so‐called vein 1A or first anal vein. It is easily identified by the unique shape of its bulla. It may have several branches and be partially fused with the cubital and anal veins. Once the PCu vein was identified, we reconsidered as an example the particular case of the Phasmatodea, showing that extant stick insects have a unique venation among insects, with a reduced median vein and a simple cubital vein adjacent or fused to the PCu vein. This study is a new approach towards resolving wing vein homology issues, crucial for future large‐scale phylogenetic analyses in insects combining extant and extinct taxa. Abstract : Insect wing venation is pivotal in systematic entomology but is still controversial, different venation patterns being used according to taxonomic groups. Using microcomputed tomography, we provide a unified wing venation pattern and demonstrate the presence of a postcubital vein (PCu) in all Neoptera between the cubital and anal veins. We clarify wing venation homologies across insect orders and use phasmids as an example to illustrate the implications of this unified wing venation pattern.